1998
DOI: 10.1097/00004647-199808000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Cerebral Hypoperfusion and Reversible Ischemia from Reductions in the Magnetic Resonance Imaging Relaxation Time, T2

Abstract: The hypothesis was tested that hypoperfused brain regions, such as the ischemic penumbra, are detectable by reductions in absolute transverse relaxation time constant (T2) using magnetic resonance imaging (MRI). To accomplish this, temporal evolution of T2 was measured in several models of hypoperfusion and focal cerebral ischemia in the rat at 9.4 T. Occurrence of acute ischemia was determined through the absolute diffusion constant D(av) = 1/3 TraceD, while perfusion was assessed by dynamic contrast imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
89
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 61 publications
(30 reference statements)
11
89
0
1
Order By: Relevance
“…Previous studies showed within the ADC lesion, qT 1 and qT 2 (5,6) change in opposite (5,6). Recent data point to two-phase response of qT 1 upon ischaemia onset; in complete forebrain ischaemia the fast response levels by two minutes (20) whereas in the core, the rapid increase lasts up to 25 minutes post MCAo (16).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies showed within the ADC lesion, qT 1 and qT 2 (5,6) change in opposite (5,6). Recent data point to two-phase response of qT 1 upon ischaemia onset; in complete forebrain ischaemia the fast response levels by two minutes (20) whereas in the core, the rapid increase lasts up to 25 minutes post MCAo (16).…”
Section: Resultsmentioning
confidence: 94%
“…Within regions of decreased ADC in rat focal ischaemia, quantitative T 2 relaxation times (qT 2 ) also decrease due to metabolic changes (6,16) and cytotoxic oedema (17). The decrease is followed by a quasi-linear increase over time (2,4) caused by altered hydrodynamics and tissue degradation (17,18).…”
mentioning
confidence: 99%
“…12 However, during the early minutes of ischemia, single Hahn echo T 2 MRI shows T 2 shortening observed both at 4.7 T and 9.4 T due to the negative blood oxygenation level-dependent effect. 18,31 Shortening of T 2 has also been reported acutely in patients imaged at 1.5 T. 32 The presence of such T 2 shortening results in a situation in which there is a time point when T 2 in the stroke tissue shows no difference to contralateral nonischemic tissue. In our data set, the ⌬T 2 zero crossover time greatly varies between striatum and cortex.…”
Section: Discussionmentioning
confidence: 93%
“…In ischemia, the earliest T 2 effect is a decrease in the relaxation time. Grohn et al, 10,11 showed that this is because of a negative blood oxygenation level-dependent effect directly related to decreased perfusion (without significant increase in CMRO 2 ), and suggested that in this context, reduced T 2 might indicate a period of ischemia in which tissue injury is fully reversible. In the current studies, perfusion was increased during sustained hypoxia, 12 and the arterial and venous compartments contain increased deoxyhemoglobin, so blood oxygenation level-dependent changes will add to the observed reduction in T 2,index .…”
Section: Diffusion-weighted Mri Changes In Acute Mountain Sickness Jsmentioning
confidence: 99%